2022
DOI: 10.3390/pathogens11010100
|View full text |Cite
|
Sign up to set email alerts
|

Avian Macrophage Responses to Virulent and Avirulent Clostridium perfringens

Abstract: The present study evaluated the avian macrophage responses against Clostridium perfringens that varied in their ability to cause necrotic enteritis in chickens. Strains CP5 (avirulent-netB+), CP1 (virulent-netB+), and CP26 (highly virulent-netB+tpeL+) were used to evaluate their effect on macrophages (MQ-NCSU cells) and primary splenic and cecal tonsil mononuclear cells. The bacilli (whole cells) or their secretory products from all three strains induced a significant increase in the macrophage transcription o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 45 publications
2
14
0
Order By: Relevance
“…To this end, the present study found that the broiler birds infected intracloacally with virulent CP18 and CP26 strains showed a significantly increased CT expression of IL-1β, IL-6, and IFNγ compared to the uninfected control and avirulent CP5-infected groups. This observation was in support of our previous studies that host inflammatory responses are often mounted against the virulent, but not avirulent, strains [ 4 , 18 ]. However, this response in CT appeared to be highly regulated when birds were infected intracloacally, as demonstrated by an increased expression of anti-inflammatory/ immunoregulatory cytokines or downregulation of expression of pro-inflammatory cytokines in the mucosal lymphoid tissues, including CT, bursa, and HG.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…To this end, the present study found that the broiler birds infected intracloacally with virulent CP18 and CP26 strains showed a significantly increased CT expression of IL-1β, IL-6, and IFNγ compared to the uninfected control and avirulent CP5-infected groups. This observation was in support of our previous studies that host inflammatory responses are often mounted against the virulent, but not avirulent, strains [ 4 , 18 ]. However, this response in CT appeared to be highly regulated when birds were infected intracloacally, as demonstrated by an increased expression of anti-inflammatory/ immunoregulatory cytokines or downregulation of expression of pro-inflammatory cytokines in the mucosal lymphoid tissues, including CT, bursa, and HG.…”
Section: Discussionsupporting
confidence: 92%
“…For example, broiler chickens coinfected with E. maxima and virulent C. perfringens induced an increased intestinal gene expression of pro-inflammatory cytokines (IL-1β, IFNγ, IL-17, IL-8, and others) [ 16 , 36 ], while in vitro stimulation of chicken intestinal epithelial cells with virulent C. perfringens or purified alpha-toxin led to an increased transcription of IL-6, IL-8, inducible nitric oxide synthase (iNOS), tumor necrosis factor (TNF), and nuclear factor kappa-B (NFkB) genes [ 37 ]. In support of these findings, macrophages have been shown as the likely source of such mucosal inflammatory responses [ 18 , 38 ] [Kulkarni, et. al., 2023; unpublished].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Single-cell splenocyte preparations (n = 8 per group) were made following a protocol described previously [ 25 ]. Briefly, the single cells were plated on 96-well round-bottom plates with each well containing 10 6 cells in 100 μL FACS buffer (PBS with 1% BSA).…”
Section: Methodsmentioning
confidence: 99%